High-efficiency K-band MMIC power amplifier using multi-harmonic load terminations. Issue 12 (December 2015) - Tu, Zhichen; Li, Bo; Shang, Yongheng; Wang, Zhiyu; Wang, Liping; Liu, Dongdong; Zhou, Min; Huang, Zhengliang; Yu, Faxin
Abstract: In this paper, a high-efficiency K-band MMIC power amplifier using multi-harmonic load terminations is designed and implemented in a 0.15 μm GaAs PHEMT processing technology. At the bias voltages of VD=5 V and VG=−0.9 V, the three-stage MMIC amplifier attains 25 dB linear gain in average, 20 dBm saturation power, lower than −15 dB input return loss, and lower than −10 dB output return loss from 25 to 27 GHz. With this 2 GHz bandwidth, the proposed amplifier can provide 40% higher power added efficiency than that of the conventional designs.